Beeswax and carnauba wax modulate the crystallization behavior of palm kernel stearin. (November 2019) - Liu, Chunhuan; Zheng, Zhaojun; Meng, Zong; Chai, Xiuhang; Cao, Chen; Liu, Yuanfa
Abstract: There is limited literature on the modulation of fat crystallization by natural waxes, which are underutilized and cost-effective food industry resources. In this study, the effects of two natural waxes (beeswax (BW) and carnauba wax (CW)) on the crystallization behavior of palm kernel stearin (PKS85) were systematically investigated by using differential scanning calorimetry (DSC), pulsed nuclear magnetic resonance ( p -NMR), X-ray diffraction (XRD) and polarized light microscope (PLM). CW addition significantly promoted the isothermal crystallization process of PKS85, especially at 20 °C, while BW had no obvious effect on the crystallization rate. BW and CW addition changed the crystal growth mode at 20 °C. BW and CW could participate in the crystallization of TAGs in PKS85, induce the formation of a new hydrocarbon chain distances of 3.70 and 4.15 Å and decrease the lamellar distance (d(001) ) and domain size (ξ) of the single crystallites, leading to a different morphology of fat crystals. Our findings indicated that BW and CW could modulate the fat crystal structure and possibly engineer the functional properties of fats and fat-structured materials, which also provided new application of natural waxes in the food industry. Graphical abstract: Image 1 Highlights: CW addition promoted the isothermal crystallization process of PKS85. BW and CW addition changed the crystal growth mode at 20 °C. BW and CW induced a new hydrocarbon chain distances of 3.70 and 4.15 Å. BW and CW decreased the lamellar distance and domain size of single crystallite. BW and CW significantly changed the crystal morphology of PKS85.